Pretreatment of papermaking‐reconstituted tobacco slice wastewater by coagulation–flocculation. Issue 2 (17th April 2013) - Wang, Yufeng; Chen, Kefu; Mo, Lihuan; Li, Jun
ABSTRACT A study using coagulation–flocculation method for the treatment of papermaking‐reconstituted tobacco slice wastewater had been carried out. Polyaluminum chloride (PAC) and polyferric sulfate (PFS) as coagulants, and four kinds of polyacrylamides (PAMs) as flocculants, were employed during the coagulation–flocculation process. The effects of three factors, that is, the dosage of coagulants, the dosage of flocculants and pH on the treatment efficiency of the process were evaluated. The results showed that the efficiencies of PAC and PFS on the reduction of COD, ammonia nitrogen (NH3‐N) and total suspended solids (TSS) in the treated effluents were equivalent; however, the efficiency of PAC on the color reduction was much higher than that of PFS. In the presence of PAC, a cationic polyacrylamide with very high molecular weight and low charge density (i.e., PAM4) was found to give the highest coagulation–flocculation efficiency. At the optimal conditions, that is, pH of 6.5, PAC dosage of 500 mg/L, and PAM4 dosage of 5 mg/L, the reductions of COD, NH3‐N, color, and TSS in the process were found to be 70.8, 84.8, 72.3, and 98.5%, respectively. The study also showed that the PAC‐PAM4 scheme can remove the most of aluminum from the raw water. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1092‐1097, 2013